2019
DOI: 10.1097/inf.0000000000002299
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Transmission of Hepatitis C Virus Among Families of Infected Pediatric Oncology Patients

Abstract: Background: Hepatitis C virus (HCV) is the most commonly encountered blood transmittable hepatitis among cancer patients. Several studies have reported clustering of HCV infections in families or household contacts of infected cases. Data about the epidemiologic aspects of intrafamilial transmission from pediatric cancer patients are scarce and still debated. We aimed to identify the magnitude of horizontal intrafamilial transmission of HCV from infected pediatric oncology patients; its prevalence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In Egypt, some studies indicated that anti-HCV prevalence in the general population was higher in males than in females (19.67% vs. 9.73%; p < 0.001) 10 , (16.1% vs. 13.4%; p < 0.001) 9 , and (7.5% vs. 5.3%; p < 0.001) 8 . While other studies found more anti-HCV prevalence in women than in men in special situations: (13.4% vs. 7.3%; p = 0.045) among family contacts of HCV-positive children 24 , (25.2% vs. 17.6%; p = 0.031) in patients with coronary heart disease 5 , and (25.1% vs. 15%; p = 0.002) in apparently healthy blood donors 3 .…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In Egypt, some studies indicated that anti-HCV prevalence in the general population was higher in males than in females (19.67% vs. 9.73%; p < 0.001) 10 , (16.1% vs. 13.4%; p < 0.001) 9 , and (7.5% vs. 5.3%; p < 0.001) 8 . While other studies found more anti-HCV prevalence in women than in men in special situations: (13.4% vs. 7.3%; p = 0.045) among family contacts of HCV-positive children 24 , (25.2% vs. 17.6%; p = 0.031) in patients with coronary heart disease 5 , and (25.1% vs. 15%; p = 0.002) in apparently healthy blood donors 3 .…”
Section: Introductionmentioning
confidence: 65%
“…By title and abstract screening, 308 studies were selected and entered the full-text screening. Only 30 studies 3 5 , 8 – 10 , 12 15 , 24 , 26 44 were finally included in our meta-analysis after full-text screening (Fig. 1 ) with 193,621 included participants: 97,597 male and 96,024 female.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, HCV infection generally occurs in people who have a history of multiple blood transfusions and does not spread by ordinary contact. Nevertheless, transmission within the family members is a possibility when sharing razors, contact with blood, and constant exposure to blood and body fluids [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sherief et al found that female caregivers, particularly mothers, contact with index cases blood. This either happens directly without using personal protective equipment or indirectly through common use of sharps (razors, scissors) and nail clippers, in addition to giving care to HCV infected cases (23) . Apart from sharing towels with relatives who are positive to HCV and handshaking/kissing with them, there is an agreement over the activities that massively contribute to infection transmission.…”
Section: Discussionmentioning
confidence: 99%